Color Management & Quality Output : Working with Color from Camera to Display to Print. - Ashe, Tom (Digital imaging masters series., 2014)
"Color Management & Quality Output tackles the most prominent problem of making a print--accurately and consistently reproducing the photographer's vision. Color management expert Tom Ashe provides in-depth, professional knowledge and thorough instructions that will enable you to create files that are color managed from input to output, properly sharpen files for a wide selection of media substrates, work with a variety of color management systems and equipment, use Photoshop for soft proofing, and experiment with a wide variety of papers and output options. This guide shows you how to achieve predictable and repeatable results for making optimal prints! As part of The Digital Imaging Masters Series, this book gives you the most cutting-edge information from the most sought-after and qualified professionals and instructors in the field. Based upon the progressive curriculum of the Masters of Professional Studies in Digital Photography at the School of Visual Arts in New York City--created by the Photoshop"